Residents’ perception on the commercialization of turtle conservation centre in Melaka. - Mohd Reazal, Syahindah; Saad, Mazni (2020)
Sea turtles have been recorded to have existed for more than 100 million years and they have played an important role in the sea environment as one to maintain the health of the ocean. However, due to the climate change and human activities, such as pollution and irresponsible tourism activities, their existence is on the verge of extinction. This has become a major problem and actions of preservation and conservation of sea turtles must be done in order to protect these creatures. To prevent the extinction of sea turtles, people need to be aware of the importance of sea turtle conservation and the threats to the turtles. The objective of this paper is to explore the perception of the residents in Melaka about the commercialization of the turtle conservation area by understanding their knowledge about turtle conservation and their take on the commercialization of the area. To achieve the objective, interview sessions with the residents of Melaka were executed to understand more about their perception. Purposive sampling technique was used where the respondents were selected among Melaka residents. The results showed that the residents supported the idea of commercialization as it benefits the residents. However, the residents were also aware of the impacts of the commercialization towards the sea turtle conservation. This paper will be significant for the study of sea turtle conservation development in the future